Ensuring Effective Functioning of Gas-Discharge Counters, Used in the Military Dose Rate Meters, in the Arctic Zone - A. V. Vasiliev; Yu. A. Glukhov; I. Y. Kulagin; K. S. Abaeva (Вестник войск РХБ защиты)
The Arctic zone is a priority area for the development and for ensuring the national security of the Russian Federation. At the same time, the region's rich natural resources create conditions for military conflicts and armed struggle of states for possession of these resources. Such conflicts might culminate with an exchange of nuclear strikes. The modern system of metrological support of military dosimetry equipment does not provide the necessary reliability of the verification and calibration procedure under low temperatures in the Arctic zone. The aim of this work is to ensure the effective functioning of gas-discharge counters, used in the military dose rate meters, in the Arctic Zone. It is established, that the reason for the low reliability of readings of military dosimeters can be the generation of false pulses due to a decrease in the suppressing ability of the counter. False impulses may appear soon after the completion of the verification. It is shown in the article, that in order to increase the reliability of measurements for devices on gasdischarge counters, it is necessary to introduce a diagnostic unit into their measuring circuit, which makes it possible to detect the presence of false pulses directly during the measurement. The implementation of the results obtained will increase the reliability of dosimetry equipment in the Far North and will also ensure greater safety of its metrological characteristics. In future, there are good reasons to conduct a study on transfer of dosimetry equipment to electronic control of gas-discharge counters in order to assess the increase in the durability of the counters and reduce the cost of their production.